Analysis of the intended mathematics curriculum revision process in Mozambique from the perspective of relevance. Issue 5 (3rd September 2021) - Kusaka, Satoshi; Nhêze, Ismael Cassamo; Baba, Takuya
ABSTRACT: The local needs and circumstances in curriculum revision often necessitate improvements in the quality of education. However, problems associated with the revision of curricula in developing countries have been observed from a range of perspectives in previous studies. This study investigates the revision process of the intended mathematics curriculum in Mozambique through document analysis of related materials and interviews with people involved in the 2015 curriculum revision. The investigation revealed three points. First, the results of nationwide surveys on academic ability conducted by the Ministry of Education and Human Development (MEHD) as well as interviews of parents and teacher questionnaires significantly affected the curriculum-revision process. Second, aligned with the political regulations, opinions from various social and economic groups worked as one of the main factors behind this process. Finally, the National Institute for Educational Development (INDE) has exhibited a strong initiative throughout the process. The research analysis would form a proposition of a methodology to analyse the curriculum revision process. The findings would be relevant to other African countries in undertaking appropriate curricular revisions.